Technological challenges in counter bioterrorism. - Laxminarayan, S. (IEEE Engineering in medicine and biology magazine)
This article focuses on bioterrorism, which plays a major role in the CBRNE arsenal because of their relative ease of delivery brought about by low visibility, high potency, and substantial accessibility.